2010
DOI: 10.1128/aac.01336-09
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of VIM-2 Reveals an Essential Determinant for Metallo-β-Lactamase Stability and Folding

Abstract: Metallo-␤-lactamase (MBL)-producing bacteria are emerging worldwide and represent a formidable threat to the efficacy of relevant ␤-lactams, including carbapenems, expanded-spectrum cephalosporins, and ␤-lactamase inactivator/␤-lactam combinations. VIM-2 is currently the most widespread MBL and represents a primary target for MBL inhibitor research, the clinical need for which is expected to further increase in the future. Using a saturation mutagenesis approach, we probed the importance of four residues (Phe-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 23 publications
0
55
0
Order By: Relevance
“…Our results were consistent with previous findings showing that A 77 V played an important role in the phenotype of expanded-spectrum cephalosporin resistance, in which A 77 V increased resistance to cefotaxime and ceftazidime when associated with P 167 and G 240 in the background of CTX-M-10 (16). Collectively, these data suggested that, albeit being located distal to the active site, A 77 V plays an important role on the catalytic activity of CTX-Ms through stabilizing the structure of the enzymes, which has also been reported in other ␤-lactamases (17).…”
Section: Resultsmentioning
confidence: 78%
“…Our results were consistent with previous findings showing that A 77 V played an important role in the phenotype of expanded-spectrum cephalosporin resistance, in which A 77 V increased resistance to cefotaxime and ceftazidime when associated with P 167 and G 240 in the background of CTX-M-10 (16). Collectively, these data suggested that, albeit being located distal to the active site, A 77 V plays an important role on the catalytic activity of CTX-Ms through stabilizing the structure of the enzymes, which has also been reported in other ␤-lactamases (17).…”
Section: Resultsmentioning
confidence: 78%
“…In order to assess VIM-2 expression, rabbit polyclonal antibodies were raised against purified VIM-2 ␤-lactamase by New England Peptide and isolated from serum using protein G column purification (Sigma Genosys, The Woodlands, TX). Sample preparation, immunoblotting, and development were performed as previously reported (29,30).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction conditions used were the following: an initial denaturation step at 96°C for 2 min; 30 cycles of denaturation at 94°C for 1 min, annealing at 48°C for 1 min, extension at 72°C for 1 min and 30 s, and a final extension step at 72°C for 20 min. The 760-bp amplification product was subcloned in the EcoRI and BamHI restriction sites of pLB-II vector (18), to obtain the pLBII-OXA-10 plasmid. The OXA-10 laboratory variants were constructed by overlapping PCR with partially overlapping primers (Table 5), as previously described (19), using the pLBII-OXA10 plasmid as the template.…”
Section: Molecularmentioning
confidence: 99%